KAJIAN KEEFEKTIFAN KAMPANYE TENTANG MENJAGA KEBERSIHAN LINGKUNGAN UNTUK GENERASI Z STUDI KASUS: GREENPEACE INDONESIA DAN KEMENTRIAN LINGKUNGAN HIDUP DAN KEHUTANAN: ANALYSIS OF THE EFFECTIVENESS OF CAMPAIGNS ABOUT MAINTAINING ENVIRONMENTAL CLEANLINESS FOR GENERATION Z CASE STUDY: GREENPEACE INDONESIA AND THE MINISTRY OF ENVIRONMENT AND FORESTRY - Ilham Ari Susanto; Drajatno Widi Utomo; Achmad Syarief (Jurnal Seni dan Reka Rancang: Jurnal Ilmiah Magister Desain, 2025)
Analysis of The Effectiveness of Campaigns About Maintaining Environmental Cleanliness for Generation Z. Environmental cleanliness is greatly influenced by the behavior of its community members, especially Generation Z, who are now becoming part of society that can take action and influence environmental cleanliness. Digital posters are one of the media favored by Generation Z for obtaining information on how to maintain environmental cleanliness. However, many digital posters aimed at teaching Generation Z about environmental cleanliness fail to capture their interest. Therefore, this study aims to identify the types of digital posters that appeal to Generation Z in campaigns for maintaining environmental cleanliness and to determine what kind of digital posters are effective for Generation Z. The effectiveness of environmental cleanliness campaigns for Generation Z aims to make digital posters more appealing to them by employing the AIDA theory, which focuses on capturing Attention, Interest, Desire, and Action, and analyzing effectiveness for poster creators discussing environmental cleanliness. Among the various creators of digital posters on maintaining environmental cleanliness, two organizations are used for comparison: Greenpeace Indonesia and the Ministry of Environment and Forestry. The conclusion of this research is that Generation Z still enjoys reading digital posters. However, the digital posters preferred by Generation Z are those created by Greenpeace Indonesia. Effective digital posters for Generation Z are those that align with their interest in digital visual works.